Pregabalin dependence: Experiences from liaison psychiatric settings in Kashmir, North India: A case series - Aaliya Khanam; Rajnish Raj; Zaid A. Wani; Yasir H. Rather; Iqra Arshad (Industrial Psychiatry Journal)
Pregabalin, a gamma-aminobutyric acid (GABA) analog, is a new-generation antiepileptic that is approved for the treatment of neuropathic pain, fibromyalgia, partial seizures, and generalized anxiety disorder. There is a rising concern regarding its abuse potential, and a handful of case reports have highlighted the same. We present a case series on pregabalin dependence. In contrast to previous case reports, which focused on patients with a history of illicit drug abuse, we present cases of drug-naïve individuals for whom pregabalin was the first substance of abuse. The highlight of the study is that we describe cases of pregabalin intoxication and a rare case of pregabalin withdrawal, which presented as a lethal suicidal attempt to liaison psychiatric settings.